2001
DOI: 10.1067/mva.2001.115000
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous fistula construction in the thigh with transposed superficial femoral vein: Our initial experience

Abstract: The SFV is an excellent conduit for vascular access, whether it is transposed or is part of a composite PTFE-SFV fistula. In this series, fistula infection was nonexistent, thrombosis rates were low, and clinical evidence of venous hypertension was minimal. The major impediment to unrestricted use of SFV in constructing AVFs is a high incidence of clinically significant postoperative ischemia requiring reoperation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 12 publications
(12 reference statements)
0
80
0
3
Order By: Relevance
“…The cumulative primary and secondary fistula patency rates were 78% and 73% at 6 and 12 months and 91% and 86% at 6 and 12 months, respectively. One patient needed above knee amputation for acute compartment syndrome, and eight patients required a second surgery for distal limb ischemia (14,15). Rueda et al (16) reported 10 patients with tFV LE-AVF accesses, and none had a lower extremity ischemic event.…”
Section: Transposed Femoral Vein Le-avfmentioning
confidence: 99%
See 1 more Smart Citation
“…The cumulative primary and secondary fistula patency rates were 78% and 73% at 6 and 12 months and 91% and 86% at 6 and 12 months, respectively. One patient needed above knee amputation for acute compartment syndrome, and eight patients required a second surgery for distal limb ischemia (14,15). Rueda et al (16) reported 10 patients with tFV LE-AVF accesses, and none had a lower extremity ischemic event.…”
Section: Transposed Femoral Vein Le-avfmentioning
confidence: 99%
“…Gradman et al (14,15) reported a low thrombosis rate in 25 patients with transposed superficial femoral vein (tFV) AVF with mean follow-up of 9.1 months. The cumulative primary and secondary fistula patency rates were 78% and 73% at 6 and 12 months and 91% and 86% at 6 and 12 months, respectively.…”
Section: Transposed Femoral Vein Le-avfmentioning
confidence: 99%
“…However, if the upper limb use is not appropriate, axillary-axillary AV access (necklace graft) (25), superficial femoral vein transposition (26), axillary artery to right atrial graft (27), hemodialysis reliable outflow graft (28), and femoral AV graft could be used as alternative choices for vascular access (19)(20)(21). Autogenous AV fistula or graft AV fistula are available for femoral AV access, although the former is not preferred because of wide incision and associated complications (19,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, autologous veins were used for constructing AVFs with transposed basilic (22) or cephalic veins in the upper limb and the great saphenous vein to form a loop in the groin, anastomosing the free end, in an end-to-side fashion, to the superficial femoral artery (23). The transposition of the superficial femoral vein appears to be burdened by several complications (24). In the early 1980s the use of optical magnification and microvascular instruments was underlined as helpful for constructing the VA (25).…”
Section: Arteriovenous Fistulas With Native Vesselsmentioning
confidence: 99%